Double‐strand DNA breaks are mainly repaired by the homologous recombination pathway in early developing swine embryos. Issue 4 (5th January 2018) - Bohrer, Rodrigo C.; Dicks, Naomi; Gutierrez, Karina; Duggavathi, Raj; Bordignon, Vilceu
Abstract : DNA double‐strand breaks (DSBs) are less frequent than single‐strand breaks but have more harmful consequences on cell survival and physiology. Homologous recombination (HR) and nonhomologous end‐joining (NHEJ) are the two main pathways that are responsible for DSB repair in eukaryotic cells, but their importance for the preservation of genome stability in totipotent blastomeres of early developing embryos has not been determined. In this study, we observed that the chemical inhibition of HR or both pathways, but not NHEJ alone, increased the number of DSBs, reduced embryo development to the blastocyst stage, and resulted in embryos with higher proportions of apoptotic cells. Targeted knockdown of ATM (ataxia telangiectasia mutated) and ATR (ataxia telangiectasia and Rad3 related; HR regulators) and DNA‐dependent protein kinase (NHEJ regulator) mRNAs revealed that the attenuation of HR or both HR and NHEJ regulators severely impaired blastocyst formation and quality. Attenuation of ATM alone resulted in a higher incidence of DSBs, lower development and embryo quality, and increased mRNA abundance of genes that are involved in either repair pathway. These findings indicate that HR is the main pathway responsible for the promotion of DSB repair in early developing embryos, and that ATM seems to be more important than ATR in the regulationofthe HR pathwayinmammalianembryos.— Bohrer, R. C., Dicks, N., Gutierrez, K., Duggavathi, R., Bordignon, V. Double‐strand DNA breaks are mainly repaired by the homologous recombination pathway in early developing swine embryos. FASEB J. 32, 1818–1829 (2018). www.fasebj.org